Effect of graphene on the self-assembly and rheological behavior of a triblock copolymer gel. Issue 102 (5th October 2015) - Zabet, Mahla; Mishra, Satish; Kundu, Santanu
Abstract : Self-assembly and the mechanical properties of graphene containing physical gels are reported in this work. Abstract : The self-assembly behavior of physical gels and the effect of such an assembly on the mechanical properties are of significant interest. Here, graphene nanoplatelets have been incorporated in a triblock copolymer gel consisting of poly(methyl methacrylate)–poly( n -butyl acrylate)–poly(methyl methacrylate) [PMMA–P n BA–PMMA] in a midblock selective solvent, 2-ethyl-1-hexanol. The thermoreversible nature of the gel allowed us to incorporate the graphene nanoplatelets in a liquid stage and these nanoplatelets then become part of the network structure as the solution is cooled. Shear rheology is used to investigate the change of mechanical properties as a function of graphene concentration. Graphene nanoplatelets affect the self-assembly behavior as demonstrated by the decrease of gelation temperature. Interestingly, no significant increase of modulus was observed with the incorporation of graphene, as typically observed in polymer nanocomposites. This indicates that the graphene nanoplatelets are not actively participating in load-bearing, i.e. the platelets are not elastically active. A small change of relaxation time in graphene containing triblock copolymer gels has been observed, as captured by stress relaxation experiments. Our results provide a method to incorporate nanomaterials in physically crosslinked polymer gels without affecting the mechanical properties significantly.